2003
DOI: 10.1093/rheumatology/keg405
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for chronic low back pain in older patients: a randomized, controlled trial

Abstract: Acupuncture is an effective, safe adjunctive treatment for chronic LBP in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 33 publications
0
81
0
6
Order By: Relevance
“…It found that the addition of acupuncture to standard treatment resulted in an improvement in disability (six weeks after treatment) and an improvement in pain (at 9 weeks, but not 6 weeks after treatment) (Meng et al 2003). Although the study was not able to demonstrate that expectations regarding treatment per se effected outcome, within the two treatment groups the patients "impressions of acupuncture" influenced their outcome within the given treatment groups (positive impressions were associated with a more positive response in the acupuncture group, whilst negative impressions led to a more positive result in standard treatment).…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…It found that the addition of acupuncture to standard treatment resulted in an improvement in disability (six weeks after treatment) and an improvement in pain (at 9 weeks, but not 6 weeks after treatment) (Meng et al 2003). Although the study was not able to demonstrate that expectations regarding treatment per se effected outcome, within the two treatment groups the patients "impressions of acupuncture" influenced their outcome within the given treatment groups (positive impressions were associated with a more positive response in the acupuncture group, whilst negative impressions led to a more positive result in standard treatment).…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…No caso das dores crôni-cas, utilizavam com frequência anti-inflamató-rios, cujo uso contínuo pode provocar reações adversas relativamente frequentes e bem conhecidas 29,30,31 . Observou-se casos de iatrogenias medicamentosas: "Eu tomei vários remédios, hoje em dia eu tenho gastrite, não é todo remédio que eu posso tomar" (E1).…”
Section: ) Quer Dizer Você Começa O Tratamento E é Interrompido (unclassified
“…Devido aos efeitos adversos de curto e longo prazos causados pelo tratamento medicamentoso e os riscos de dependência, principalmente em patologias crônicas, nossos achados e outros estudos da literatura 31 indicam que a acupuntura pode contribuir para diminuir a polimedicação e as iatrogenias medicamentosas, além de melhorar a potência do cuidado. Kooreman & Baars 36 mostraram não só menores custos com o uso de outras racionalidades médicas (acupuntura, homeopatia e medicina antroposófica) em pacientes da atenção primária à saúde europeia, como também maior longevidade dos mesmos.…”
Section: "Durante Um Ano Fazendo Acupuntura Consegui Ficar Três Meseunclassified
“…This was represented as Figure 1 in Somerville et al's report as a stable trajectory. 1 We have done a new analysis of data from the UK BEAM trial 4 (Brealey et al 5 in the original paper), extracting data on outcomes for those in the usual care group of this trial with pain lasting for more than 3 months (n = 205). Furthermore, we obtained data from the usual care arm of Licciardone et al's trial of osteopathic manipulation (thanks to John Licciardone).…”
Section: 3mentioning
confidence: 99%
“…1 They highlight the variability that currently exists in the usual care packages, which function as the comparator treatment in many trials, and point out that the content of treatment in this arm is often inadequately described. They draw our attention to the difficulties associated with the interpretation of results when this comparator treatment is poorly described.…”
mentioning
confidence: 99%